A novel and consistent method (TriPOD) to characterize an arbitrary porous solid for its accessible volume, accessible geometrical surface area and accessible pore size - Herrera, L.; Fan, Chunyan; Do, D.; Nicholson, D. (Springer, 2011)
We present an improved Monte Carlo integration method to calculate the accessible pore size distribution of a porous solid having known configuration of solid atoms. The pore size distribution obtained with the present method is consistent with the accessible volume and the accessible geometric surface area presented in previous publications (Do and Do, in J. Colloid Interface Sci. 316(2):317-330, 2007; Do et al. in Adsorpt. J., 2010). The accessible volume, accessible geometrical surface area and the pore size distribution method construct an unambiguous and robust single framework to characterize porous solids. This framework is based on the derivation of the space accessible to the center of mass of a probe molecule. The accessible pore size presented is an absolute quantity in the sense that a zero value is possible. We present the entire framework of this characterization method and compare the improved method with the one presented previously for a set of porous solids such as graphitic slit pores, defective slit pores, bundle of carbon nanotubes, zeolite and some metal organic frameworks. © 2010 Springer Science+Business Media, LLC.